Contracting-out and governance mechanisms in the public employment service - Oliver Bruttel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
The contracting-out of job brokerage and case management services is a major international trend in the reform of the Public Employment Service. Instead of a public agency, private providers are contracted to deliver these services for the jobseekers. Australia and the Netherlands have contracted-out (almost) all of this formerly core public service. The U.K. has introduced so-called Employment Zones, in which private providers are responsible for long-term unemployed and thus replace the public Jobcentre Plus for this target-group. Based on agency theory, the paper analyses and compares the contract management in the three cases with respect to the risk of moral hazard. Differentiating between three distinct governance mechanisms (incentives, information and control), the paper shows the requirement of an integrated approach to contract management. – – Das Contracting-out der öffentlichen Arbeitsvermittlung und des Fallmanagements für Langzeitarbeitslose ist eine der wesentlichen internationalen Entwicklungen in der Reform der öffentlichen Arbeitsverwaltung. Statt einer öffentlichen Behörde werden dabei private Anbieter vertraglich beauftragt, diese Dienstleistungen für Arbeitssuchende zu erbringen. Australien und die Niederlande sind bei dieser Auslagerung ehemals öffentlicher Dienstleistungen besonders weit gegangen. Großbritannien hat so genannte 'Employment Zones' eingerichtet, in denen private Anbieter für Langzeitarbeitslose zuständig sind und somit die Leistungen des Jobcentre Plus für diese Zielgruppe ersetzen. Ausgehend von der Prinzipal-Agent-Theorie analysiert und vergleicht der Aufsatz das Vertragsmanagement in den drei Ländern hinsichtlich des Moral Hazards. Ein effektives Governance-Konzept erfordert, dass die drei wesentlichen Steuerungsinstrumente (Anreiz-, Informations- und Kontrollmechanismen) zu einem integrierten Vertragsmanagement zusammengeführt werden.
Keywords: 330; Arbeitsvermittlung; Outsourcing; Personalberatung; Vertrag; Agency Theory; Lieferanten-Kunden-Beziehung; Australien; Niederlande; Großbritannien